Direct shear and direct simple shear tests: a comparative study of the strength parameters and their dependence on moisture and fines contents - Babalola, Zainab (Department of Civil Engineering, 2016)
Shear strength of soil is characterized by cohesion, angle of internal friction and dilatation. The first two parameters mentioned primarily define the soil's ability to resist shear stress underspecified load. These parameters can be determined by tests conducted either in the laboratory or the field for use in design of geotechnical structures. Some of the tests in the laboratory to determine the shear strength of soil, include triaxial, ring shear, torsional shear, direct shear and direct simple shear. Direct shear test is the most widely used geotechnical shear device due to its simplicity, however, the test suffers from stress inhomogeneity. Direct simple shear apparatus was developed because of the shortcomings in the direct shear test. In these two tests, different shearing conditions are applied to soil samples. For the direct shear test, shearing occurs at a predetermined center of the specimen which may not be the weakest plane of the soil while indirect simple shear, the entire specimen distorts without the formation of single shearing surface. The mode of shearing established in the direct simple shear device is similar to that which occurs around the shaft of a pile. In contrast to the extensive geotechnical application of direct shear test, limited information exists on direct simple shear test. This thesis endeavours to establish the relationship between the two tests by undertaking extensive testing to obtain a better understanding of direct simple shear test as used for testing local soils and to determine a correlation with the results from direct shear tests. A series of shear tests were undertaken on Klipheuwel sand, Kaolin clay and composite of the sand and clay using universal shear device. The soils were mixed with water in percentages of 5,10, 15, 20 and 25%, and the composite with clay percentages of 10, 25, 50 and 75%, to investigate the impact of water and clay on the shear parameters determined from the two tests. The results showed that direct shear test gives higher shear strength when compared to direct simple shear test under the same soil condition. The addition of water, and clay, generally reduced the internal friction angle of sand for both tests. Furthermore, increase in cohesion was observed with the addition of water to Kaolin clay for the direct simple shear test and the reverse was true in the direct shear test. The correlation factors developed in this study for the direct simple shear test could be used to refine the results from the direct shear test.